Association of predicted pathogenic mutations in mitochondrial ND genes with distant metastasis in NSCLC and colon cancer. Issue 1 (December 2017) - Koshikawa, Nobuko; Akimoto, Miho; Hayashi, Jun-Ichi; Nagase, Hiroki; Takenaga, Keizo
Abstract Cancer cells have more mutations in their mitochondrial DNA (mtDNA) than do normal cells, and pathogenic mutations in the genes encoding mitochondrial NADH dehydrogenase (ND) subunits have been found to enhance the invasive and metastatic ability of various tumour cells in animal experiments. However, it is unknown whether single-nucleotide variants (SNVs) of theND genes that decrease complex I activity are involved in distant metastasis in human clinical samples. Here, we demonstrated the enhancement of the distant metastasis of Lewis lung carcinoma cells by theND6 13885insC mutation, which is accompanied by the overexpression of metastasis-related genes, metabolic reprogramming, the enhancement of tumour angiogenesis and the acquisition of resistance to stress-induced cell death. We then sequencedND genes in primary tumour lesions with or without distant metastases as well as metastatic tumour lesions from 115 patients with non-small cell lung cancer (NSCLC) and colon cancer, and we subsequently selected 14 SNVs with the potential to decrease complex I activity. Intriguingly, a significant correlation was observed (P  < 0.05 by Chi-square test) between the incidence of the selected mutations and distant metastasis. Thus, these results strongly suggest that pathogenicND gene mutations participate in enhancing distant metastasis in human cancers.